Structure–Function Relationships of Glycoprotein Hormones and Their Subunits’ Ancestors - Cahoreau, Claire; Klett, Danièle; Combarnous, Yves (Frontiers in Endocrinology, 2015)
Glycoprotein hormones (GPHs) are the most complex molecules with hormonal activity. They exist only in vertebrates but the genes encoding their subunits ancestors are found in most vertebrate invertebrate species although their roles are still unknown. In the present report we review the available structural and functional data concerning GPHs and their subunits’ ancestors.